Post-fire recovery of soil organic carbon, soil total nitrogen, soil nutrients, and soil erodibility in rotational shifting cultivation in Northern Thailand - Arunrat, Noppol; Sereenonchai, Sukanya; Kongsurakan, Praeploy; Iwai, Chuleemas Boonthai; Yuttitham, Monthira; Hatano, Ryusuke (Frontiers in Environmental Science, 2023)
The hill tribes in Thailand traditionally depend on rotational shifting cultivation (RSC). However, insufficient understanding remains on post-fire soil properties and soil erodibility (k-values) with fallow years. To address this gap, the levels of soil organic carbon (SOC), soil total nitrogen (STN), soil nutrients, and soil erodibility after fire in RSC were investigated. Topsoil (0–10 cm) samples from sites with 4 (RSC-4Y), 5 (RSC-5Y), and 7 (RSC-7Y) fallow years in Chiang Mai Province, northern Thailand, were taken at four time points: before burning, 5 min after burning, 9 months after burning, and 2 years after burning. Soil pH, electrical conductivity, and soil nutrient (available P, K, and Ca) levels were increased after burning and remained higher than the pre-burning levels for at least 2 years. The SOC stock decreased after burning in all fallow fields. At 2 years after burning, the SOC stock in RSC-4Y was higher than before burning, whereas in RSC-5Y and RSC-7Y, the levels had not reached the pre-fire levels. The STN stocks of all studied fields significantly decreased after burning and had not reached the pre-burning levels after 2 years. After burning, the topsoil of RSC-4Y was most susceptible to erosion. However, only in RSC-4Y, the k-value was unchanged at 2 years after burning. Three different approaches are recommended for post-fire land management: 1) farmers should not cut and remove the weeds and grasses at the soil surface, 2) burning should be performed around late winter or early summer (November–February) to inhibit complete combustion, and 3) contour-felled log erosion barriers should be made by using the trunks remaining after the fire to trap the sediment and slow down surface runoff.